A Rationale in Support of Uncontrolled Donation after Circulatory Determination of Death. (18th December 2012) - Munjal, Kevin G.; Wall, Stephen P.; Goldfrank, Lewis R.; Gilbert, Alexander; Kaufman, Bradley J.; Dubler, on behalf of The New York City uDCDD Study Group, Nancy N.
Abstract Most donated organs in the United States come from brain dead donors, while a small percentage come from patients who die in "controlled, " or expected, circumstances, typically after the family or surrogate makes a decision to withdraw life support. The number of organs available for transplant could be substantially if donations were permitted in "uncontrolled" circumstances–that is, from people who die unexpectedly, often outside the hospital. According to projections from the Institute of Medicine, establishing programs permitting "uncontrolled donation after circulatory determination of death, " or uDCDD, throughout the United States has the potential to provide 22, 000 more donation opportunities annually. In contrast, U.S. controlled donation after circulatory determination of death, or cDCDD, cases have increased progressively over the past decade from 87 to 848 donors, but currently account for only 10.6 percent of all deceased donors. Following the IOM recommendations, several projects exploring the feasibility of uDCDD were funded by the federal government, including a grant from the Health Resources and Services Administration that supported a pilot project in New York City in which the authors of this article participated. A key feature of our protocol, and indeed of many uDCDD protocols, is the initiation of preservation methods such as chest compressions and extracorporeal membrane oxygenation shortly after death in order to perfuse and preserve the donor's organs. Critics of uDCDD argue that the means of determining death deviates from generally ascribed principles. They assert that reinstituting circulation in order to preserve organs has the effect of "undoing" the prior determination of death. The result is that cDCDD is widely accepted and practiced routinely even though it only marginally increases the number of organs available for transplantation, and uDCDD is widely considered unacceptable despite being ethically embraced and proven to significantly increase organ donation opportunities in other countries. This article explores the evolution of this counterintuitive state of affairs and calls for a policy that, in line with the IOM report, allows for both cDCDD and uDCDD protocols.